Menakar Konstitusionalitas Penunjukan Penjabat (Pj) Kepala Daerah dalam Masa Transisi Demokrasi - Guanti, Wiwin (AL-SULTHANIYAH, 2025)
The vacancy of positions in hundreds of autonomous regions following the expiration of definitive regional heads’ terms has been addressed by the central government through a massive, centralized, and prolonged regime of appointing Acting Officials (Penjabat, Pj). This paper offers a comprehensive juridical-normative analysis of the constitutionality of this mechanism, focusing on the tension between administrative discretion (freies ermessen) and the principle of popular sovereignty. The study examines the coherence of Minister of Home Affairs Regulation (Permendagri) No. 4 of 2023 with the mandates of Constitutional Court Decisions No. 67/PUU-XIX/2021 and No. 15/PUU-XX/2022, as well as evaluates the phenomenon of “administrative dual function” through the placement of active TNI/Polri officers. The findings reveal that the absence of implementing regulations at the level of Government Regulation (PP) and the lack of meaningful participation have degraded the quality of regional autonomy, created a legitimacy deficit, and opened opportunities for abuse of power that undermine the principles of a democratic rule of law.